Total otolaryngology-head and neck surgery - Dyleski, Robin A.; Linstrom, Christopher J.; Pitman, Michael Jay; Schaefer, Steven D.; Schantz, Stimson P.; Shin, Edward J. (Thieme Medical Publishers, Inc., 2015)
Total OtolaryngologyHead and Neck Surgery is a comprehensive otolaryngology reference that presents a consistent approach to the diagnosis and treatment of head and neck disorders. It provides thorough coverage of basic science topics as well as concise, practical information on clinical topics, such as radiographic imaging of common clinical presentations, deep neck infections, transoral robotic surgery, surgery of the aging face, lasers in laryngology, and much more. Key Features: Opening section on emergency management containing key information residents need for emergency room rotations